Economic analysis of the business model for mass seed production of nutrient-dense small indigenous fish species mola (Amblypharyngodon mola) - Chand, Bimal; Dubey, Sourabh; Panemangalore, Arun; Gaikwad, Amar; Das, Rashmi; Gogoi, Kalpajit; Rajts, Francois (Wiley, 2025)
Small indigenous fish species, such as mola carplet (Amblypharyngodon mola), play a crucial role in the diets of fish-dependent populations in India due to their rich micronutrient content. Recognized as a key species for promoting nutrition-sensitive aquaculture, mola has recently been successfully bred in hatcheries using standardized induced breeding and mass seed production protocols. This study assesses the economic viability of integrating mola seed production into an existing carp hatchery in Odisha, India. A comprehensive financial analysis, including cost-return assessment, bankability, economic performance, break-even analysis, and sensitivity testing, was conducted. The proposed model has a production capacity of 1 million seeds per cycle, with 24 cycles annually. The total investment required is INR 4,12,932 ($4,975), comprising capital expenses of INR 2,56,650 ($3,092) and annual operational costs of INR 1,56,282 ($1,883) considering loan component. The business model demonstrates strong profitability, with an operational profit margin of 53.57% at a selling price of INR 1,000 ($12) per 100,000 hatchlings. The break-even point is achieved at 17 production cycles per year and INR 885 ($10) of per unit of seeds price. Financial indicators confirm high viability, with a benefit-cost ratio of 1.67, a net present value of INR 2,28,233 ($2,750), and an internal rate of return of 32.94%. The model is also bankable, evidenced by a debt service coverage ratio of 1.63, and remains profitable under various sensitivity scenarios. These findings highlight the potential for integrating mola seed production into existing carp hatcheries, offering a scalable and sustainable approach to strengthening small indigenous fish farming and advancing nutrition-sensitive aquaculture in India.